2023
DOI: 10.3390/pharmacy11010022
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Pharmacist Perspectives on Utilizing a Personalized Family Medication Safety Plan for Opioid Education with Adolescents and Parents

Abstract: Background: Exposure to prescription opioids during adolescence is associated with an increased risk of future opioid misuse. The pervasive and growing impact of the opioid epidemic requires evidence-based, co-designed interventions targeted at adolescents. MedSMA℞T Families is an intervention tailored to educate adolescents and their families about opioid misuse prevention and consists of two parts: the MedSMA℞T: Adventures in PharmaCity videogame and the family medication safety plan (FMSP). Objective: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Pharmacists were shown the FMSP 1.0 and offered their feedback. 31 Overall, the pharmacists in our study supported the use of the FMSP in their consultation practices while asserting that it would have little impact on their pharmacy’s workflow. They reported that the information included on the FMSP was accurate and the covered topics were important to opioid medication safety.…”
Section: The Personalized Family Medication Safety Plan (Fmsp)mentioning
confidence: 73%
See 1 more Smart Citation
“…Pharmacists were shown the FMSP 1.0 and offered their feedback. 31 Overall, the pharmacists in our study supported the use of the FMSP in their consultation practices while asserting that it would have little impact on their pharmacy’s workflow. They reported that the information included on the FMSP was accurate and the covered topics were important to opioid medication safety.…”
Section: The Personalized Family Medication Safety Plan (Fmsp)mentioning
confidence: 73%
“…Parents evaluated the FMSP 1.0 for its potential use in their families’ medication management practices. 32 Parents saw potential for the FMSP to be used when bringing home new medications or for family members who take multiple medications simultaneously. The content and sections were favorable to parents and represented information they suggested to be important.…”
Section: The Personalized Family Medication Safety Plan (Fmsp)mentioning
confidence: 99%